PENGAWASAN KEPALA DESA TERHADAP KINERJA RT 06/RW 03 DESA RAMBAH JAYA KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU TAHUN 2015-2016 - Agus Riyanto; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Rokan Hulu District Government seeks to recreate a participatory RT and RW organization that is mobilized by the community itself. With this regional regulation, the Rokan Hulu government tries to create democracy in the smallest scope of neighborhoods of RT and RW while providing legitimacy to the elected head of RT and RW. This research intends to examine the issues of Performance RT 06 / RW 03 Desa Rambah Jaya from the point of view, the implementation of supervision and evaluation.This study aims to determine the implementation of Village Head supervision on the performance of RT 06 / RW 03 Village Rambah Jaya District Bangun Purba Rokan Hulu District. In addition, this study aims to determine the factors that affect the implementation of supervision of Village Head on Performance RT 06 / RW 03 Village Rambah Jaya District Bangun Purba Rokan Hulu District. This research uses the supervision theory by Dharma Setiawan Salam. The type of research used is descriptive research with qualitative approach. Methods of data collection is done by interview, observation and documentation.The results of this study showed that the Head of Rambah Jaya Village conducted Intensive Communication, Head of Rambah Jaya Village conducted supervision in the form of accountability and Head of Rambah Jaya Village conducted supervision in Democratic Participatory Creation and Head of Rambah Jaya Village to conduct transparency supervision. The factors influencing the implementation of Village Head supervision on the performance of RT 06 / RW 03 Rambah Jaya Village is the Resource Factor, the absence of regulations / regulation from the Village Government related to the Village Head's supervision on RT / RW Performance and Member Errors /deviations RT 06 / RW 03 requires supervision from Rambah Jaya Village Head.Keywords: Implementation, Supervision, Village Head